078 Effective meetings- how to improve productivity of meetings. (December 2018) - Pilkington, C; Soar, D; Baugh, N; Stojanovic, J; Katugampola, H; Hoskins, S
Abstract : Effective Meetings: Introduced by Sheffield MCA (Flow Coaching Academy), effective meetings aim to ensure all participants can be engaged in a non-hierarchical discussion, whilst finishing meetings on time. The first meeting establishes the groups ground rules. For instance, respectful listening, mobiles on silent and non-judgemental. Four roles are needed: Chair Time–keeper Note–keeper and Facilitator At the start of each meeting, participants volunteer to undertake a role. The meeting starts by setting the agenda. Times are then agreed to discuss each item so that the meeting ends on time. The chair guides the meeting through the agenda. The timekeeper warns the chair and/or participants when each item is drawing to a close. The record-keeper takes notes for feedback or adds notes to a flipchart to keep a visual record of progress during the meeting for the team. This allows action points to be tracked. The facilitator ensures that everyone has a chance to speak, including prompting those who normally remain silent. Five minutes before the end of the meeting, an evaluation takes place. Each participant is asked to score the meeting out of 10. Each participant is asked for one comment on what went well and/or one comment of how the meeting could be improved. Effective meetings have been used in the Great Ormond Street 'Big Room' improvement projects and have been adopted for many of the Rheumatology team meetings. Over the course of 4 months, meetings have become measurably more productive and more enjoyable as shown below. Meeting In April 2018 Evaluation average 3.83/10. Meeting in July 2018 Evaluation average 8.31/10.